ANALISIS EFEKTIFITAS PAJAK RESTORAN DAN HUBUNGANNYA DENGAN PENDAPATAN ASLI DAERAH KABUPATEN SANGGAU - Budiono B01107103, Agus Iman (Jurnal Pembangunan dan Pemerataan, 2014)
This researchgets title â€œPotency and Effectiveness of Restaurant Taxes Analisis at Sanggau Regency in Year period 2006-2011,â€ by Agus Iman Budiono, are one case study research on on duty financial Management Income and Region Asset (DPPKAD) Sanggau's regency. The aim of this research is subject to be know and analizing of restaurantâ€™s taxes acceptance effectiveness and its influence to PAD (original regional revenue) at Sanggau Regency in year period 2006 until 2011. This is descriptive observational analisis, with ratio measurement method effectiveness with effectiveness of Depdagri indicator (2004). The analisis's tool is utilized a pearson correlation (product moment) by data that is utilized is time series data (2006 - 2011). Variable that is utilized is effectiveness and PAD. The result observationaling to point out that taxeses regressive effectiveness restaurant up to period 2006 2011 averages as big as 137.13 %. bases depdagri's criterions so effective. Supreme effectiveness to be reached on year 2006 by 181,13% meanwhile bottommost are on 2010 77,02. The low effectiveness of tax revenue in 2010 due to arrears are still many who have not / are not collectible. The results of correlation analysis showed that the relations are negative, but the relationship is not significant, means an increase or decrease in the realization nothing to do with the effectiveness of a restaurant tax. Keyword: restaurant taxes, effectiveness, PAD